Simultaneous Kinetic Spectrophotometric Determination of V(IV) and V(V) by H-point Standard Addition Method - Zarei, Kobra; Atabati, Morteza; Golmohammadi, Maryam (Asian Journal of Chemistry, 2010)
The H-point standard addition method was applied to kinetic data for simultaneous determination of V(IV) and V(V) or selective determination of V(IV) in presence of V(V). The method is based on the difference in the rate of complex formation between V(IV) and V(V) with methyl thymol blue. The linear dynamic ranges for the two analytes of V(IV) and V(V) are 0.18-3.15 and 0.25-4.00 μg mL-1, respectively. The proposed method was successfully applied for the determination of vanadium in two different oxidation states in several synthetic mixtures and also in blood serum and water samples.